The effect of recombinant human growth hormone with or without rosiglitazone on hepatic fat content in HIV-1 infected individuals; a randomized clinical trial - Kotler, Donald P (Antivir Ther, 2014)
BACKGROUND: Hepatic fat is related to insulin resistance (IR) and visceral adipose tissue (VAT) in HIV+ and uninfected individuals. Growth hormone (GH) reduces VAT but increases IR. We evaluated the effects of recombinant human GH (rhGH) and rosiglitazone (Rosi) on hepatic fat in a substudy of a randomized controlled trial. METHODS: HIV+ subjects with abdominal obesity and IR (QUICKI ≤ 0.33) were randomized to rhGH 3 mg daily, Rosi 4 mg twice daily, the combination, or double placebo. Hepatic fat was measured by magnetic resonance spectroscopy (MRS), visceral fat by MRI, and IR by frequently sampled IV glucose tolerance tests at baseline and week 12. RESULTS: 31 subjects were studied at both time points. Significant correlations between hepatic fat and VAT (r = 0.41, p=0.02) and QUICKI (r = 0.39, p<0.05) were seen at baseline. Insulin resistance rose with rhGH but not Rosi. When rhGH treatment groups were combined, hepatic fat expressed as percent change decreased significantly (p<0.05) but did not change in Rosi (p=0.71). There were no correlations between changes in hepatic fat and VAT (p=0.4) or QUICKI (p=0.6). In a substudy of 21 subjects, a trend was noticed between changes in hepatic fat and serum IGF-1 (p=0.09). CONCLUSIONS: Hepatic fat correlates significantly with both VAT and IR, but changes in hepatic fat do not correlate with changes in VAT and glucose metabolism. Hepatic fat content is reduced by rhGH but Rosi has no effect. These results suggest an independent effect of growth hormone or IGF-1 on hepatic fat. The study was registered at Clinicaltrials.gov (NCT00130286).